2021
DOI: 10.3390/medicina57111282
|View full text |Cite
|
Sign up to set email alerts
|

Classification and Morphometric Features of Pterion in Thai Population with Potential Sex Prediction

Abstract: Background and Objectives: The landmark for neurosurgical approaches to access brain lesion is the pterion. The aim of the present study is to classify and examine the prevalence of all types of pterion variations and perform morphometric measurements from previously defined anthropological landmarks. Materials and methods: One-hundred and twenty-four Thai dried skulls were investigated. Classification and morphometric measurement of the pterion was performed. Machine learning models were also used to interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
(38 reference statements)
1
5
0
1
Order By: Relevance
“…Bilateral occurrence is statistically insignificant. The study conducted by Uabundit N [11] in 100 dry skulls. The PMP distance, or the distance between the pterion center to the mastoid process of the temporal bone, was significantly longer in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral occurrence is statistically insignificant. The study conducted by Uabundit N [11] in 100 dry skulls. The PMP distance, or the distance between the pterion center to the mastoid process of the temporal bone, was significantly longer in males.…”
Section: Discussionmentioning
confidence: 99%
“…Skulls with pathologies such as porotic hyperostosis were also excluded. The morphometric measurements were carried out by measuring the distance from the centre of the pterion to six different locations of the skull including, distance from the center of the pterion to the anterior aspect of the frontozygomatic suture -PSFZ, distance from the center of the pterion to the zygomatic angle -PZAN, distance from the center of the pterion to the zygomatic arch -PZA, distance from the center of the pterion to Henle's spine-PH, distance from the center of the pterion to the mastoid process of the temporal bone -PMP, distance from the center of the pterion to the external occipital protuberance -PI[Figure . 1] [9,10,11,12].…”
Section: Methodsmentioning
confidence: 99%
“…No significant gender difference was observed in terms of type and laterality of various pterions. The study by Uabundit N [18], 124 Thai dried skulls were investigated and reported Sphenoparietal type was the most common type (62.1%), followed by epipteric (11.7%), fronto-temporal (5.2%) and stellate (1.2%). Complete synostosis of the pterion suture was present in 18.5% and was only present in males.…”
Section: Discussionmentioning
confidence: 99%
“…Data was collected using a data tool adopted from Nongnut Uabundi for social demographic information from the catalogue of bones in the laboratory and distances were recorded in millimeters (Uabundit et al, 2021). The skulls were obtained and assessed for eligibility by the investigator assisted by an expert anatomist and a technician.…”
Section: Data Collectionmentioning
confidence: 99%